Mechanical Properties of Marble Under Triaxial and Cyclic Loading Based on Discrete Elements - Yanshuang Yang; Jiancheng Peng; Zhen Cui; Lei Yan; Zhaopeng Kang (Applied Sciences)
The excavation process for a deeply buried chamber in a high ground stress area is often dynamic. The design of reasonable excavation methods for differing geological conditions and surrounding pressure environments is of great engineering significance in order to improve the stability of surrounding rocks during construction. Based on the findings from conventional triaxial and cyclic loading laboratory tests on marble, this paper obtains a set of mesoscopic parameters that accurately represent the macro-mechanical characteristics of marble, uses the discrete element method (DEM) to establish a numerical model, and carries out numerical tests of triaxial and cyclic loading under varying circumferential pressures. The mechanical parameter evolution, crack propagation mechanism and mesoscopic force field distribution of marble under conventional triaxial stress and cyclic load-reversal conditions are compared and analyzed. The findings suggest that the peak strength, residual strength, peak axial strain, elastic modulus, and Poisson’s ratio of marble increase as the circumferential pressures rises for both stress paths. The peak strength and elastic modulus under cyclic loading at different circumferential pressures are lower than those observed under conventional triaxial conditions, while the Poisson’s ratio is higher compared to conventional triaxial conditions. The cumulative total number of microcracks in marble damage under cyclic loading is higher and the damage is more complete compared to conventional triaxial loading. The rock specimens in both stress paths are dominated by tension cracks. Nevertheless, a greater number of shear cracks are exhibited by the specimens subjected to cyclic loading conditions. The proportion of tension cracks in the rock specimens gradually decreases with increasing circumferential pressure, while the proportion of shear cracks gradually increases. For both stress paths, the angular distribution of microcracks following rock specimen failure is similar, and the force chain becomes progressively denser as the circumferential pressures increase. The force chain distribution within the rock specimens is more heterogeneous under cyclic loading conditions than under conventional triaxial conditions.